The responses of international company’s stock return in Malaysia / Nurul Liyana Mohamad Fadzillah - Mohamad Fadzillah, Nurul Liyana (2010)
Established companies in Malaysia with good characteristics in handling business may have the potential to spread their business to the international level. The exchange rate is one of the factors which will be a focus on international trading. The exchange rate can be defined as “the charge for exchanging currency of one country for currency of another”. Other definition is “the amount of one currency that a person or institution defines as equivalent to another when either buying or selling it at any particular moment”. For example, when importing items from the USA, we used USD rate as the mean of transaction through intermediaries such as banks. The theory of dividend and its effect on the value of the firm is perhaps one of the most important yet puzzling theories in the field of finance. By declaring a dividend yield as a factor, it might be exposing the firms’ performance in trading activities. Like earnings, dividends act as proxy for the future profitability. Besides from that, other factors of economic variables are also bringing impact on the stock return of firm which is determined as factors of firm’s performance. For this study, the researcher investigates a debt ratio, P/E ratio and book to market value ratio that perform firms’ revenue. All these factors will create an expectation to the investors to compare with other multinational companies in Malaysia. It also can be used to evaluate a company based on its assets, such quality, services and others. A company also can hire a certified accountant, economist, or statistician to help them evaluate a company's debts or equity. This will force a manager to make a decision without objective function. Choosing the wrong objective function can be disastrous to the company. These factors are known as distress risk to financial companies on their return. There are consisting of ratio that examine from financial statement of company that would estimate the firms’ performance.